Optimization of Corneal Epithelial Progenitor Cell Growth on Bombyx mori Silk Fibroin Membranes - Thomas A. Hogerheyde; Shuko Suzuki; Jennifer Walshe; Laura J. Bray; Sally A. Stephenson; Damien G. Harkin; Neil A. Richardson (Hindawi Limited, 2016)
Scaffolds prepared from silk fibroin derived from cocoons of the domesticated silkworm moth Bombyx mori have demonstrated potential to support the attachment and growth of human limbal epithelial (HLE) cells in vitro. In this study, we attempted to further optimize protocols to promote the expansion of HLE cells on B. mori silk fibroin- (BMSF-) based scaffolds. BMSF films were initially coated with different extracellular matrix proteins and then analysed for their impact on corneal epithelial cell adhesion, cell morphology, and culture confluency. Results showed that collagen I, collagen III, and collagen IV consistently improved HCE-T cell adherence, promoted an elongated cell morphology, and increased culture confluency. By contrast, ECM coating had no significant effect on the performance of primary HLE cells cultured on BMSF films. In the second part of this study, primary HLE cells were grown on BMSF films in the presence of medium (SHEM) supplemented with keratinocyte growth factor (KGF) and the Rho kinase inhibitor, Y-27632. The results demonstrated that SHEM medium supplemented with KGF and Y-27632 dramatically increased expression of corneal differentiation markers, keratin 3 and keratin 12, whereas expression of the progenitor marker, p63, did not appear to be significantly influenced by the choice of culture medium.